58 Excluding treg epitopes and integrating CD8 and CD4 effector neoepitope content improves prognostic biomarker tool in bladder cancer. (9th November 2020) - Richard, Guilhem; Steinberg, Gary; Garcia, Tzintzuni; Ardito, Matthew; Martin, William; Berdugo, Gad; Princiotta, Michael; Balar, Arjun; Groot, Anne de; Sweis, Randy
Abstract : Background: Improvement of current prognosis biomarkers will enhance our ability to identify cancer patients at higher risk of recurrence and will further advance the personalization of patient monitoring and treatment. We hypothesized that the presence of a mutation alone is not sufficient to generate an immunogenic neoepitope, but that significant differences must exist between the Human Leukocyte Antigen (HLA)- and/or T Cell Receptor (TCR)-interfaces of the neoepitope and its non-mutated form, or with other self-epitopes, in order to be recognized as non-self by the immune system. As such, cancer patient clinical outcomes may be better understood by neoepitope analyses that integrate these considerations. Methods: We analyzed large scale (n=412) bladder cancer genomic data from The Cancer Genome Atlas (TCGA) using Ancer, an automated machine-learning-based pipeline we designed for neoantigen screening and vaccine design. Ancer shares components with other commercial-grade screening platforms used routinely in immunogenicity assessments of biologics and infectious disease antigens, such as the EpiMatrix algorithm for HLA-I and HLA-II neoepitope identification, and the JanusMatrix algorithm for tolerated, tolerogenic, and cross-reactive T cell epitope identification. Evaluation of patient survival with Ancer was compared to other analyses employing tumor mutational burden (TMB) or neoepitopes identified with the commonly used NetMHCpan-4.0 and NetMHCIIpan-3.1 T cell epitope prediction tools. Results: We stratified bladder patients based on their Ancer HLA-I and HLA-II neoepitope burdens and observed significantly prolonged disease free and overall survival in patients whose tumor contained both high numbers of HLA-I and HLA-II neoepitopes compared to other individuals. Stratifications performed with Ancer were superior to comparative analyses performed with TMB or with NetMHCpan and NetMHCIIpan. In addition, we showed that Ancer's precise filtering and characterization of mutated epitopes contributed to this increased association with survival, as showcased by gradual improvements in survival analyses performed after each of its filtering step. Multivariate survival analyses indicated that Ancer neoepitope content remained a significant factor in patient overall survival even when adjusted for TMB, and other clinical covariates such as age at diagnosis and disease stage, unlike analyses involving NetMHCpan and NetMHCIIpan neoepitopes. Conclusions: Our analysis suggests that enhanced presence of CD8, CD4 T cell epitopes, and limited inclusion of Treg epitopes in the tumor genome plays a key role in cancer survival. Ancer scoring provides a predictive method for predicting patient outcomes, by defining the number of true neoepitopes and by identifying Treg epitopes that would interfere with T cell-based immune activation and response to the tumor.